Cheias de charme : como a teledramaturgia se reinventou na era da transmídia - Jardine, Cora Netto (2015)
The Internet has transformed the reality of brazilian television, and changed the way of watching its programming. Aligned with a research published in 2015 by the Ministry of Communication that indicates that 42% of the population is connected at least four hours a day to the Internet, Rede Globo has been testing a new model of television drama based on the transmedia storytelling. Such phenomenon constitutes in a trend that shows a new stage of involvement between the receptor and the products of entertainment offered. The success of Cheias de Charme, the 7pm soap opera broadcasted by Rede Globo in 2012, is the result of an experiment that overlapped a fiction environment to a simulated reality scenario. In that context, the viewer is stimulated to move along the several platforms where the plot develops (television, radio, websites and social networks) in a way to fulfill the whole of the plot. Capable of uniting the two contexts (the real and the pseudo-fiction), the Internet was used as a mean (1) and as an object of soap opera. In the first hypothesis (1) it serves as a link between the two atmospheres where the plot develops. In the second (2), the world wide web is addressed as a theme in the script itself, being treated as agent of social transformation, mainly when the phenomenon empreguetes was propelled. This dissertation has as an objective to comprehend the transmedia strategies adopted by the soap opera Cheias de Charme for the launching of the clip Vida de Empreguete. From the content analysis techniques (Bardin, 2009) applied to the body of seven chapters and the materials published on the web – (www.globo.com/cheiasdecharme) and social networks that surround the clip, it was possible to identify the importance of the usage of Internet in the ambience of the soap opera (fiction) as well as outside of it (pseudo-reality and reality).